Dinos among the dunes: Dinoturbation in the Pirambóia Formation (Paraná Basin), São Paulo State and comments on cross-section tracks - Christofoletti, Beatriz [UNESP] (2021)
Soft-sediment deformation structures are conspicuous features found in both ancient and modern, shallowly buried, loose, and water-saturated sediments related to diverse depositional environments. Numerous triggering mechanisms can induce their development, including seismicity, glaciotectonics, overload, and bioturbation. The presence of soft-sediment deformation in the Jurassic fluvial-eolian Pirambóia Formation has been known for a long time and was usually associated with seismic-induced triggers. Recently described synsedimentary structures in wet interdune deposits from the lower part of this unit, close to its type area in São Paulo State, southeastern Brazil, are now interpreted as true cross-section tracks produced by large tetrapods based on examples from the literature and morphological analyzes. Based on their age, size, and comparisons with dinosaur tracks described in Jurassic lithostratigraphic units from Paraná Basin in Brazil (Guará Formation) and Waterberg Basin (Etjo Formation), we suggest here, for the first time, that some of those deformational structures were produced by dinosaurs. Furthermore, the cross-section tracks from the Pirambóia Formation in São Paulo State exceed in size the tracks with therapsid affinity described in the Permian-Triassic unit in southern Brazil, hindering their full correlation. This finding may potentially represent the oldest evidence of the presence of dinosaurs in the São Paulo State territory, expanding our knowledge of the poorly known Jurassic tetrapod fauna of Brazil. Additionally, these cross-section tracks reinforce the possible correlation, at least in part, of the Pirambóia Formation in its northern occurrence (near to its type area) with the Jurassic Guará Formation from southern Brazil.